Attenuation of Oxidative Stress by Cannabinoids and Cannabis Extracts in Differentiated Neuronal Cells - Aruna Raja; Soha Ahmadi; Fernanda de Costa; Nan Li; Kagan Kerman (Pharmaceuticals, 2020)
In this proof-of-concept study, the antioxidant activity of phytocannabinoids, namely cannabidiol (CBD) and Δ9- tetrahydrocannabinol (THC), were investigated using an in vitro system of differentiated human neuronal SY-SH5Y cells. The oxidative stress was induced by hydrogen peroxide, as reactive oxygen species (ROS). Alzheimer’s disease (AD)-like pathological conditions were mimicked in vitro by treating the differentiated neuronal cells with amyloid-β1–42 (Aβ1–42) in the presence of Cu(II). We showed that THC had a high potency to combat oxidative stress in both in vitro models, while CBD did not show a remarkable antioxidant activity. The cannabis extracts also exhibited a significant antioxidant activity, which depended on the ratio of the THC and CBD. However, our results did not suggest any antagonist effect of the CBD on the antioxidant activity of THC. The effect of cannabis extracts on the cell viability of differentiated human neuronal SY-SH5Y cells was also investigated, which emphasized the differences between the bioactivity of cannabis extracts due to their composition. Our preliminary results demonstrated that cannabis extracts and phytocannabinoids have a promising potential as antioxidants, which can be further investigated to develop novel pharmaceuticals targeting oxidative stress therapy.